Influence of Vertical Diversification on Sustainable Organizational Performance of Chartered Private Universities in Kenya (International Journal of Scientific Research and Management (IJSRM), 2024)
The worldwide higher education sector has been revolutionized by globalization, adverse economic circumstances, intense industrial rivalry, and the changing demands of the contemporary customer. Private universities are compelled to reconsider their tactics. The present research investigates the implementation of vertical diversification as a crucial approach that private universities might use to achieve sustained organizational performance. The research used a cross-sectional survey approach, including the whole population of 21 private institutions in Kenya. The study used primary data collection via the use of structured research questionnaires. The acquired data was quantified and analyzed using descriptive and inferential statistics via the use of the Statistical Package for Social Sciences (SPSS). The research used Analysis of Variance (ANOVA) to determine the connection between the variables, while correlation and regression analyses were utilized to examine hypotheses and the associations among the variables. The inferential analysis demonstrated a clear and direct correlation between horizontal diversification and the sustainable performance of private institutions in Kenya. Moreover, the research confirmed a statistically significant and beneficial impact of implementing a horizontal diversification strategy on the sustainable performance of private institutions in Kenya. The study recommended that policymakers should consider formulating and implementing policies that encourage and support vertical diversification in chartered private universities in Kenya. Private universities should strategically embrace vertical diversification practices to enhance sustainable organizational performance. This involves continuous efforts to upgrade existing programs, diversify academic offerings, and establish programs that meet the evolving needs of industries.